Role of pretreatment fluorodeoxyglucose positron emission tomography quantitative parameters in prognostication of head-and-neck squamous cell carcinoma - Narayana Subramaniam; Deepak Balasubramanian; P Shanmuga Sundaram; Samskruthi Murthy; Krishnakumar Thankappan; Subramania Iyer (Indian Journal of Medical and Paediatric Oncology)
In spite of the good organ preservation strategies available for locally advanced head-and-neck squamous cell carcinoma (HNSCC), failure rates have been reported to be as high as 35%–50%. There has been an increasing interest in predicting response to treatment, to aid early intervention and better outcomes. Fluoro-2-deoxy-D-glucose-positron emission tomography (FDG-PET) is a standard modality for posttreatment evaluation; however, it is still underutilized as a pretreatment investigative modality. Several articles have described quantitative parameters in pretreatment FDG-PET to prognosticate patients and determine the likelihood of response to treatment; however, they are still not used commonly. This article was a review of the literature available on pretreatment FDG-PET quantitative parameters and their value in predicting failure. A thorough review of literature from MEDLINE and EMBASE was performed on pretreatment quantitative parameters in HNSCC. Metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were reliable parameters to predict response to organ preservation therapy, disease-free survival, and overall survival. Maximum SUV (SUVmax) was an inconsistent parameter. MTV and TLG may help predict poor response to organ preservation to initiate early surgical salvage or modify therapeutic decisions to optimize clinical outcomes. Routine use may provide additional information over SUVmax alone.